Eastern State Penitentiary - Gordon, Nick (Minneapolis, MN : Bellwether Media, Inc., 2013)
"Engaging images accompany information about the Eastern State Penitentiary. The combination of high-interest subject matter and light text is intended for students in grades 3 through 7"--Provided by publisher.
Provides information on the legends and the history of Eastern State Penitentiary of Pennsylvania.
Something lurks -- Hard time -- Haunted halls -- Eastern State Penitentiary today.
Includes bibliographical references and index.
Keywords: Eastern State Penitentiary of Pennsylvania -- Miscellanea -- Juvenile literature; Eastern State Penitentiary of Pennsylvania -- History -- Juvenile literature; Eastern State Penitentiary of Pennsylvania; Eastern State Penitentiary of Pennsylvania; Haunted prisons -- Pennsylvania -- Juvenile literature; Ghosts -- Pennsylvania -- Juvenile literature; Haunted prisons -- Pennsylvania; Ghosts -- Pennsylvania; Haunted houses -- Pennsylvania; Ghosts -- Pennsylvania